PENETRASI KAPITALIS DAN RESISTENSI PETANI: KASUS SENGKETA AGRARIA DI TANAH LIDO KABUPATEN BOGOR, JAWA BARAT - Widiono, Septri (Jurnal AGRISEP, 2008)
This research was aimed to study about an agrarian conflict at Lido land. In order to get the comprehensive its meaning the qualitative approach with the case study strategy were used. The conflict explained as the dialectical relation among peasants in the one hand and the agrotourism company in the other hand. The conflict taken place with the support of local government to the company while peasants made patronize relationship with the NGO. The dynamic of agrarian conflict has meaning of capitalist penetration and the peasant resistency.